2018
DOI: 10.32474/cdvs.2018.01.000106
|View full text |Cite
|
Sign up to set email alerts
|

Pressure of Climatic Factors on Sheep Bluetongue Epidemics in Tamil Nadu

Abstract: This research correlates the effect of climatic factors on bluetongue epidemiology in sheep of delta districts in Tamilnadu based on merteriological data collected from 2014 to 2016. There were a total of eighty two villages of delta districts were affected with Blue tongue virus (BTV). We used multiple linear regression analysis to assess the effect of climatic factors on the prevalence of bluetongue. Our results showed that maximum temperature, rain fall and relative humidity positively correlates with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The result showed a remarkable difference (p<0.01) in the seroprevalence of BTV antibodies at different locations of the study areas. This might be due to diverse climatic condition of Darchula including hot and humid temperature following monsoon that favours for the vector growth and activity (Kumar et al, 2018). Moreover, the district share open boarder with India and China, where several outbreaks of bluetongue disease have been reported ( Joardar et al, 2013;Bitew et al, 2013;Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The result showed a remarkable difference (p<0.01) in the seroprevalence of BTV antibodies at different locations of the study areas. This might be due to diverse climatic condition of Darchula including hot and humid temperature following monsoon that favours for the vector growth and activity (Kumar et al, 2018). Moreover, the district share open boarder with India and China, where several outbreaks of bluetongue disease have been reported ( Joardar et al, 2013;Bitew et al, 2013;Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…C. kumbaensis from the south-west region was replaced by C. distinctipennis in this study, although both species have previously been reported in former British Southern Cameroon [ 4 , 13 ]. These differences in species diversity and abundance may be influenced by the type of ecosystem, ecological alterations, periods of collection or the proximity of other animals [ 26 , 27 ]. For instance, the presence of C. distinctipennis in the rain forest area of the Littoral Region may be accounted for by the presence of boggy ground that is thinly covered with grass and decumbent plants [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…They occur during the late summer and autumn closely related to climatic and ecological factors which in turn influence the abundance and survival of the vectors. These factors include temperature (Wittman et al, 2002), vegetation index (Carpenter et al, 2009), relative humidity (Carpenter et al, 2009;kumar et al, 2018), wind speeds (Ducheyne et al 2007;Carpentier et al, 2008;Baylis et al, 2010), higher rainfall in the preceding month of the occurrence of the disease (Gloster et al, 2008;Eticha andMekonne, 2019), elevation (Hendricks et al, 2008;Guis et al, 2012), livestock distribution (van Schaik et al, 2008Jacquot et al, 2017 ) and soil types (Purse et al, 2004). There are many dynamic climate zones in Tunisia with different agriculture practices and different livestock distribution among regions.…”
Section: Introductionmentioning
confidence: 99%